New methods for indexing multi‐lattice diffraction data. (1st October 2014) - Gildea, Richard J.; Waterman, David G.; Parkhurst, James M.; Axford, Danny; Sutton, Geoff; Stuart, David I.; Sauter, Nicholas K.; Evans, Gwyndaf; Winter, Graeme
<x xml:space="preserve">Abstract</x> A new indexing method is presented which is capable of indexing multiple crystal lattices from narrow wedges of diffraction data. The method takes advantage of a simplification of Fourier transform‐based methods that is applicable when the unit‐cell dimensions are known a priori. The efficacy of this method is demonstrated with both semi‐synthetic multi‐lattice data and real multi‐lattice data recorded from crystals of ∼1 µm in size, where it is shown that up to six lattices can be successfully indexed and subsequently integrated from a 1° wedge of data. Analysis is presented which shows that improvements in data‐quality indicators can be obtained through accurate identification and rejection of overlapping reflections prior to scaling.